Phytochemical compounds in the methanolic extract of piper Betle l. Leaves - Mohd Azlan, Mawaddah; Mohammad, Mardhiah (The Malaysian Society of Applied Biology, 2018)
Piper betle L. or known as ‘Sireh’ in Malaysia has been useful in treating various conditions. This study aimed to investigate the phytochemical compounds present in Piper betle L. methanolic extract using Gas Chromatography-Mass Spectrometry (GCMS) and Liquid Chromatography-Mass Spectrometry (LCMS). Plant leaves were ground into powder and soaked in methanol for 15 days. Extract was filtered and concentrated using a rotary evaporator before analyses. GCMS and LCMS have identified ten and 26 compounds respectively. Phenols was identified as the major component of the extract in both analyses. A new major phytocomponent was discovered in this study and recognized as actinidioinoside when identified by LCMS. This study has discovered the presence of phytocomponents with therapeutic importance, which can further be studied and be used in future treatments.